2016
DOI: 10.1002/jor.23328
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin suppresses microglial activation and reduces the development of neuropathic pain after spinal cord injury

Abstract: Rapamycin is an inhibitor of the mammalian target of rapamycin (mTOR) signaling pathway, plays an important role in multiple cellular functions. Our previous study showed rapamycin treatment in acute phase reduced the neural tissue damage and locomotor impairment after spinal cord injury (SCI). However, there has been no study to investigate the therapeutic effect of rapamycin on neuropathic pain after SCI. In this study, we examined whether rapamycin reduces neuropathic pain following SCI in mice. We used a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 58 publications
(186 reference statements)
3
55
0
Order By: Relevance
“…Tateda S et al demonstrated that rapamycin, as an inhibitor of mTOR, suppressed the development of neuropathic pain when the spinal cord was injured [36]. These studies consisted with our observation that the inhibition of mTOR can significantly attenuate symptoms of neuropathic pain.…”
Section: Discussionsupporting
confidence: 56%
“…Tateda S et al demonstrated that rapamycin, as an inhibitor of mTOR, suppressed the development of neuropathic pain when the spinal cord was injured [36]. These studies consisted with our observation that the inhibition of mTOR can significantly attenuate symptoms of neuropathic pain.…”
Section: Discussionsupporting
confidence: 56%
“…In microglia (CD11/OX42+), mTOR signaling is increased in response to oxidative stress, hypoxia, and cytokines including TNFα [49] and IL-1β, and modulates the production of nitric oxide [117]. mTOR signaling could also contribute to activation of microglia, as blockade of mTOR with rapamycin decreases numbers of activated microglia [118, 119]. Therefore, increases in p-mTOR-positive astrocytes in the voluntary exercise condition could contribute to the beneficial effects of exercise on neuronal health and plasticity, whereas an increase of p-mTOR-positive microglia following forced wheel running could be a consequence of, or contributor to, cellular stress and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Rapamycin has been used as an anticancer and immunosuppressive agent in clinical treatment (Populo et al, 2012; Tateda et al, 2017). Because the side effects from rapamycin are relatively low compared to with other drugs, it has also been widely used in chronic pain treatments (Lee et al, 2006; Alamo et al, 2009).…”
Section: Discussionmentioning
confidence: 99%